FORMATION OF ANOSOVITE DURING CARBOTHERMAL REDUCTION OF LEUCOXENE - Nazarova L.Y.; Istomin P.V.; Askhabov A.M. (My University, 2007)
Titanium oxides occupy a special place in the production of composite materials. The most promising way to obtain these materials is the reworking of natural titanium raw material. In this work, we attempted to synthesize the high-temperature Ti3O5 modification by carbothermal reduction of leucoxene from the unique Yareg titanium deposit, Komi Republic. The Yareg deposit is composed of metamorphic rocks including predominant schists and quartzitelike sandstones. The subordinate limestones, marls, tuffites, and dolerites occur as stratal bodies or are confined to the fault zones. The placer in the lower unit contains more than 40 various minerals. The major mineral of the heavy fraction is leucoxene (45–49%) of the quartz–rutile nature-rutile grains embedded in a quartz matrix, thus forming a natural composite.
Keywords: anosovite